APPLICABILITY AND QUALITY ASSESSMENT OF THE SET OF EQUIPMENT IN THE PROJECT “POLYGON FOR PHYSICAL ACTIVITY OF SCHOOL-AGED CHILDREN“ IN PRIMARY SCHOOLS WITHOUT GYMNASIA (Kinesiology, 2020)
In 2015, 120 central primary schools in Croatia failed to meet the minimum requirements, and could not carry through the full-time compulsory Physical Education class. To ensure daily habits for physical exercise in all children and help teachers, Croatian Institute of Public Health has designed a Set of kinesiological aids and implemented the project “Polygon for Physical Activity of School-Aged Children”. The aim of this paper is to present the results of Project evaluation.Project evaluation has shown improved conditions and increased pupil interest in Physical Education. A statistically significant difference (χ2=65,30, df=4, p